Dexter by design [large type] - Lindsay, Jeffry P. (Thorndike Press large print core, 2009)
Back from his surprisingly glorious honeymoon in Paris, Miami blood spatter analyst Dexter Morgan is one step closer to perfecting his human disguise. However, old habits die hard and Dexter's work for the Miami Police Department never fails to offer up new playmates--bad men who appeal to his offbeat and unshakable sense of justice.